Cave of forgotten dreams [videorecording (DVD)] - Herzog, Werner, 1942- (IFC Films, 2011)
A breathtaking new documentary from the incomparable Werner Herzog, follows an exclusive expedition into the nearly inaccessible Chauvet Cave in France, home to the most ancient visual art known to have been created by man. An unforgettable cinematic experience that provides an unique glimpse of pristine artwork dating back to human hands over 30,000 years ago, almost twice as old as any previous discovery.